The blind [videorecording (DVD)] - Hyatt, Andrew, 1982-; Katz, Stephanie (Screenwriter); Dasher, Zach; Andrian, Aron von; Eve, Amelia; White, Matthew Erick; Robillard, Brielle; Tillman, Connor; Ales, John; Carroll, Ronan; Abinante, Scarlett; Knuppe, Kerry, 1983-; et al. (Mill Creek Entertainment, 2023)
Set in the 1960s South and shot on location in Louisiana, THE BLIND shares never-before-revealed aspects of Phil Robertson's life as he seeks to conquer the shame of his past, addiction, and complicated family dynamics, ultimately finding redemption in an unlikely place. "It was important to us that the film be real," said Willie Robertson, Phil's son. "The transformation of Phil proves that anyone can change and that there is always hope."